Sensor-Based Turmeric Finger Growth Characteristics Monitoring Using Embedded System under Soil - Maheswaran Shanmugam; Asokan Ramasamy (International Journal of Distributed Sensor Networks)
Modern agribusiness is becoming increasingly reliant on computer-based systems which was formerly performed by humans. One such technological innovation is the embedded system-based sensor array module such as flex sensor, temperature sensor, and pH sensor that have been used to monitor the turmeric finger growth characteristics. The experimental work has been tested with five different nodes and the average flex sensor resistance changes in five nodes are calculated. Among the five nodes, nodes II and V were diseased. Purposely node II was left as such and node V was treated with Pseudomonas and viride to restrict the Rhizome rot disease attack. As a result, after cultivation, it was found that the Rhizome rot disease attack on node V is comparatively lesser than node II. The greatest advantage of this method is that it helps the farmers to detect the Rhizome rot disease and also prevent it an early stage by monitoring the growth of the turmeric fingers when it is under the soil.